Industrial policy of Nigeria : policies, incentives, guidelines, and institutional framework - Nigeria (Abuja, Nigeria : Federal Ministry of Industries, Federal Secretariat, 1989)
This document is meant to address uncertainty about the policy environment, a restrictive and cumbersome regulatory framework and inadequate incentives.
aia 21/03/2019
Loans
Keywords: Industrial policy; Nigeria